Bibliometric Analysis of Research on Mathematics Anxiety in Two Decades - Irvan (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2023)
Mathematical anxiety has plagued all levels of math students. Bibliometric analysis is required due to the absence of quantitative research in this field's publications. Employing 496 Scopus literature, this research investigated the evolution of publications pertinent to mathematics anxieties in learning. The descriptive and network analysis software applications Biblioshiny and VOSviewer are utilized. Over the past 20 years, the results demonstrate that the aggregate trend of publications in this field has increased by 25% annually. Frontiers in Psychology is ranked first among publications. The most influential author, E.A. Maloney, had 832 citations and publications. The United States surpassed all other nations in terms of contribution. The article "Mathematics Anxiety and the Affective Decline in Performance" by MH Ashcraft ranks first in annual total and average citations. Psychology and the educational process in college, the primary factors for the emergence of mathematical anxiety, and elementary school math knowledge are the most popular themes among researchers. Given that math anxiety can potentially impair learning, this study aids readers in gaining a deeper understanding of the current corpus of research.